Quantum Optical Analysis of Atomic Density and Refractive Index Employing Cavity Enhanced Absorption Spectroscopy (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
We propose a novel cavity enhanced absorption spectroscopic technique to sensitively measure atomic density and refractive index of a sample gas.We theoretically investigate the quantum optical response of a gas of atoms enclosed inside an optical cavity to a probe beam that passes through it. In particular, we study the intracavity spectra, the output spectra and the spectra of the fluctuations. We show that the response of the system is sensitive to small changes in the number of atoms and the refractive index.
Keywords: Quantum optical response; Cavity enhanced absorption spectroscopy; Fluctuation dynamics